THE IMPACT OF DIGITALIZATION ON ENTREPRENEURSHIP - Oliveira, Xavier; Silva, Pedro (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2023)
This article intends to analyse and critically discuss the state of the art of scientific literature concerning digitalisation and its impact on entrepreneurship. The study adopts a systematic literature review, relating the concepts, studying their impact on economic development, and enumerating the variables that may serve as indicators. Data was collected using the Prism method, which allowed a total of 561 articles (from 2006 to 2022) which 13 were used for analysis. The article guides researchers towards a better understanding of the concepts through the systematisation of several investigations carried out so far, also allowing the delineation of the relations between both and their impact on economic development. The articles are clustered into the following themes: i) the relationship between entrepreneurship and digitalisation; ii) the impact of digitalisation and entrepreneurship on economic development; iii) variables that may serve as gauges of the impact on economic development.